Response of mustard (Brassica juncea L.) varieties to different levels of plant spacings and fertilizer: Response of mustard (Brassica juncea L.) varieties to different levels of plant spacings and fertilizer - BEENA NAIR,; J R KATORE,; S R KAMDI,; D D MANKAR, (Journal of Oilseeds Research, 2020)
Plant height, number of branches/plant, siliqua/plant, yield/plant and seed yield were not significantly influenced by the spacing. Variety TAM-108-1 recorded significantly higher siliqua/plant, seed yield/plant and seed yield than ACN-9. 150% RDF resulted in significant higher seed yield.